Gender Roles in Corrections: How Gendered Expectations Impact Female Correctional Officers - Hermary, Samantha (MacEwan University Student eJournal, 2024)
Compared to other organizations within the criminal justice system, the world of corrections is hidden from public view, and therefore, quickly forgotten. However, like many of these male-dominated organizations, there are significant issues regarding gender and women's roles in the job. With the considerable lack of research regarding correctional officers within Canada and the relatively small percentage of women in the correctional workforce, it is vital to expand this topic to understand the complication of a gendered role. Research has shown gendered issues among female correctional officers and the lack of the support they may receive. With all these persistent issues, we ask ourselves, why do women continue a career path that appears to be working against them? More specifically, how does gender influence women's experience in long-term careers in corrections? To answer this, I conducted in-depth qualitative interviews with women who maintained long-term roles in Correctional Service Canada (CSC). This presentation will discuss these women's gendered experiences working within a masculine organization, how their gender affected their relationships and job expectations, and how CSC may view them.